Q. 153.9( 11 Votes )

In the given figu

Answer :

To Prove: ∆ACB ∆DCE

Proof:


Given that, 1 = 2


DBC = DCE


Also in ∆ABC & ∆DCE, we get


DCE = ACB [they are common angles to both triangles]


And


Or


Or [ BD = DC as 1 = 2]


Thus by SAS-similarity criteria, we get


∆ACB ∆DCE


Hence, proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses